The long Good Friday - Hanson, Barry; Mackenzie, John, ]e direction; Hand Made Films; Calender Production ([London] : Hand Made Films, 2006)
Just as he is about to go legit, a gangster learns of a mysterious threat to his underworld kingdom
Title from title screen
Director of photography, Phil Meheux ; music, Francis Monkman ; editor, Mike Taylor
Cast: Bob Hoskins, Helen Mirren, Dave King, Bryan Marshall, Derek Thompson, Eddie Constantine, Paul Freeman
DVD format
Keywords: Gangster films; Feature films